Grinding performance using variants of the MQL technique: MQL with cooled air and MQL simultaneous to the wheel cleaning jet - Lopes, Jose Claudio [UNESP] (2019)
The hardening of legislation in favor of socio-environmental preservation and the sustainable focus of industry are changing the current manufacturing methods, among which is grinding. This abrasion machining technique aims to produce parts with excellent surface finish and high geometric precision. On the other hand, the multiple sharp edges of the abrasive grains that make up the grinding wheel simultaneously deform and shear the workpiece surface material, which releases a lot of energy in the form of heat. In this context, to soften the damage caused by the high temperatures, cutting fluids are applied to lubricate and refrigerate the tool/workpiece interface during the grinding process. However, the use of these fluids is damaging to people's health and carries a high cost for disposal, given their potential to impact the biosphere. In this sense, the society allied with the researchers seeks alternative methods of lubri-refrigeration, among them, the minimum quantity lubrication (MQL), which applies a small quantity of fluid to the cutting zone through a flow of compressed air. However, the excessive increase of machining temperatures and the intensification of the grinding wheel clogging are significant drawbacks of this technique. Thus, to mitigate these problems, this work seeks to evaluate the traditional MQL application, MQL with cooled air (MQL+CA), and assisted by a wheel cleaning jet (MQL+WCJ), comparing them with the conventional method with abundant fluid, in the external cylindrical plunge grinding of the AISI 4340 steel using an aluminum oxide grinding wheel. The output parameters used to assess the efficiency of the techniques were surface roughness, roundness error, diametrical wheel wear, grinding power, tangential cutting force, specific grinding energy, and microhardness. The machined surfaces were evaluated through optical and scanning electron microscopies to verify possible thermal damages and microstructural alterations, and optical microscopy images of the grinding wheel cutting surface were assessed to ascertain the occurrence of the wheel clogging phenomenon. The results of the tests showed that the conventional method produced the best results in all analyzed parameters. Besides, MQL+WCJ and MQL+CA outperformed all the results obtained with traditional MQL, which revealed the improvement obtained with these eco-friendly techniques and their applicability in the industry. Moreover, the application of the MQL+WCJ provided the closest results in comparison with the conventional method, proving to be superior to the MQL+CA.